The Association between Social Functions and Quality of Life among Elderly in Denpasar - Nandini Parahita Supraba; Ni Putu Widarini; Luh Seri Ani (Universitas Udayana, 2016)
Background and purpose: Good quality of life among elderly will reduce social and economic burden among the productive age people. This study aims to determine association between social function and quality of life among elderly in Denpasar. Methods: A cross-sectional survey was conducted among 144 elderly in Denpasar who were selected by cluster sampling and data were collected by a structured interview. Data were analyzed using logistic regression to determine the relationship between quality of life of the elderly with social activities, social interactions and family functions. Results: The study showed that the proportion of lower quality of life of the elderly in Denpasar was 64.58%. Proportion of elderly with lower quality of life was found among elderly of older age, female, low education, not working, low-income and widow/widower. Multivariate analysed showed that there was an association between quality of life of elderly with gender (AOR=6.42; 95%CI: 1.79-23.0), employment (AOR=9.81; 95%CI: 2.45-39.1), health status (AOR=8.65; 95%CI: 2.57-29.02), social activities (AOR=3.85; 95%CI: 1.22-12.1), social interactions (AOR=5.59; 95%CI: 2.01-15.5) and family functions (AOR=21.7; 95%CI: 6.09-77.7) Conclusion: Good quality of life of elderly was found associated with gender, employment, health status, social activities, social interactions and family functions.